Effective forms of teaching a foreign language in modern society - Nusrat, Murguzova Lamia; Beybala, Mammadova Aynur; Gafarova, Gulnar Abulfaz (Technium Social Sciences Journal, 2023)
The effectiveness of the educational process increases the use of various forms of teaching in foreign language lessons. An information search in scientific and pedagogical sources led to the conclusion that there is no clear definition of the concept of "forms of education" in pedagogical science. In the explanatory dictionary of S. I. Ozhegov, the concept of "form" is interpreted as a type, device, type, structure, construction of something due to a certain content. I.M.Cheredov defines the form as a special construction of the educational process, the nature of which is determined by its content, methods, techniques, means, types of student activities.